MACHINING PROPETIES OF COCONUT PALM WOOD - R. A. Juson (International Coconut Community Journal, 1987)
Kiln dried coconut lumber with 16 percent average moisture content were subjected to five common wood working processes composed of planing, boring, shaping, turning and sanding. Tungsten carbide cutters were used in each process except in sanding where silicon no. 60 sandpaper was employed. The coconut lumber measuring 25 mm thick by 125 mm wide by 1.25 m long have density range of 200 to 900 kg. per cubic meter.